2012
DOI: 10.3109/08923973.2012.693086
|View full text |Cite
|
Sign up to set email alerts
|

Effect of all-transretinoic acid (ATRA) on syndecan-1 expression and its chemoprotective effect in benzo(α)pyrene-induced lung cancer mice model

Abstract: All-trans retinoic acid (ATRA), an active metabolite of retinal, has been shown to exert anti-cancer activities in a number of cancer cells and tissues. Syndecan-1 is a proteoglycan, mediate cell-cell adhesion and prevent invasion in epithelial cells. The aim of the present study was to examine the level of syndecan-1 expression and the chemopreventive effect of ATRA during lung cancer development in BALB/c mice. Syndecan-1 expression was examined by immunohistochemistry using mouse monoclonal anti-human synde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…It is noted that myeloma and pancreatic chemotherapeutic drugs tend to induce accumulation of shed SDC-1 exactly as benzo(α)pyrene does in lung cancer. To avoid such tumor initiating effect, the use of metalloproteinase inhibitors in combination with chemotherapy and all-trans retinoic acid was suggested (153, 157). Another strategy to accomplish shedding inhibition involves the use of SST0001, a non-anticoagulant heparin with anti-heparanase activity, whose use diminishes the heparanase-induced SDC-1 shedding.…”
Section: Potential Syndecan-based Pharmacological Approaches In Cancementioning
confidence: 99%
“…It is noted that myeloma and pancreatic chemotherapeutic drugs tend to induce accumulation of shed SDC-1 exactly as benzo(α)pyrene does in lung cancer. To avoid such tumor initiating effect, the use of metalloproteinase inhibitors in combination with chemotherapy and all-trans retinoic acid was suggested (153, 157). Another strategy to accomplish shedding inhibition involves the use of SST0001, a non-anticoagulant heparin with anti-heparanase activity, whose use diminishes the heparanase-induced SDC-1 shedding.…”
Section: Potential Syndecan-based Pharmacological Approaches In Cancementioning
confidence: 99%
“…Syndecan-1 is a proteoglycan that mediates cell-cell adhesion and prevents invasion in epithelial cells. Retinoic acid may increase syndecan-1 expression to block invasion/metastasis of lung cancer [ 37 ]. Notably, retinoic acid has been found to reduce chemotherapy-induced neuropathy in an animal model as well as patients with lung cancer [ 38 ].…”
Section: Retinoic Acid and Lung Cancermentioning
confidence: 99%
“…All-trans retinoic acid, an active metabolite of retinal, has been shown to exert anticancer activity against different cancer cells. It has been reported that benzo(α)pyrene induces accumulation of shed SDC1 in lung cancer [ 155 ]. One study examined the level of SDC1 expression and the chemopreventive effect of all-trans retinoic acid in a benzo(α)pyrene-induced lung cancer model in BALB/c mice.…”
Section: Introductionmentioning
confidence: 99%
“…One study examined the level of SDC1 expression and the chemopreventive effect of all-trans retinoic acid in a benzo(α)pyrene-induced lung cancer model in BALB/c mice. The results indicated that all-trans retinoic acid inhibited lung tumor development and reduced SDC1 expression in cancer cells [ 155 ]. It has been reported that bFGF/FGF2 induces shedding of SDC1 in cancer cells [ 156 ].…”
Section: Introductionmentioning
confidence: 99%